Effects of prefabricated ankle orthoses on postural stability in basketball players with chronic ankle instability - Faraji, E.; Daneshmandi, H.; Ebrahimi Atri, A.; Onvani, V.; Rezaee Namjoo, F. (Asian Journal of Sports Medicine, 2012)
Purpose: Ankle sprain is one of the most common injuries among athletes and Instability and injury to this joint is responsible for almost long time lost from physical and recreational activity. Also it can impose high cost to sport teams. Prevention of this injury is an important concern of practice and rehabilitation. One way of reducing the possibility of ankle joint injury is using ankle orthosis. The present study aimed at inspecting the effects of two ankle orthoses on dynamic and semi-dynamic postural stability in athletes with chronic ankle instability.